Adapting Speaking Etiquette in Digital Intercultural Communication: A Bibliometric Analysis - Muhammad Akhyar Aji Saputra; Alma Vorfi Lama (Journal of Social Studies and Education, 2025)
This research explores the evolving role of speaking etiquette in intercultural communication within the digital age. With the increasing shift from face-to-face communication to virtual platforms, traditional norms of communication etiquette are undergoing significant changes. The study addresses the challenge of adapting these norms, traditionally rooted in non-verbal cues and in-person interactions, to digital environments where communication is primarily text-based or mediated through video conferencing. Using a bibliometric approach, this research analyzes trends in the literature on speaking etiquette and intercultural communication, mapping the intersection of key concepts such as digital literacy, emotional intelligence, and cultural adaptation. The findings highlight a clear shift toward incorporating technological and emotional intelligence skills into traditional communication practices. Additionally, the research identifies a gap in the literature regarding the adaptation of speaking etiquette to digital platforms, suggesting that future research should explore these interactions in greater depth. The study's implications underscore the need for updated communication strategies that integrate digital competencies to improve intercultural interactions in an increasingly digital world. These insights provide a foundation for enhancing global communication practices, particularly in multicultural and virtual settings.